Comparative intake of bone meal and calcium phosphate mineral mixtures as phosphorus sources for grazing steers and lactating cows - F. Brazle; Gerry L. Kuhl; T. Wary; Dale L. Lanham (Kansas Agricultural Experiment Station Research Reports, 1983)
Steers on native grass consumed equal amounts of mixtures containing 50% trace mineralized salt and either 50% bone meal or 50% calcium phosphate. Lactating cows consumed about 60% more of the bone meal:salt mixture. This research verifies that both products are palatable supplemental phosphorus sources and that choice of product should be a function of cost per unit of phosphorus.
Keywords: Cattlemen& #x27; s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Bone meal; Calcium phosphate; Steers; Lactating cows